2014
DOI: 10.1111/jam.12418
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel method for detection ofClostridium difficileusingHSSPMEGCMS

Abstract: Aims: A novel method has been developed that allows successful differentiation between Clostridium difficile culture-positive and culturenegative stool samples based on volatile organic compound (VOC) evolution and detection by headspace solid-phase microextraction coupled with gas chromatography mass spectrometry (HS-SPME-GC-MS). Methods and Results:The method is based on the activation of p-hydroxyphenylacetate decarboxylase produced by Cl. difficile and the detection of a specific VOC, that is 2-fluoro-4-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Addition of this substrate resulted in a high sensitivity and specificity (Table 2). In absence of 2-fluoro-4-methylphenol, discrimination was not possible between C. difficile positive and negative samples [20]. In addition, three other studies demonstrated that, by means of GC-MS, C. difficile positive fecal samples could be distinguished from controls based on their VOC profiles.…”
Section: Infectious Diseasesmentioning
confidence: 91%
See 1 more Smart Citation
“…Addition of this substrate resulted in a high sensitivity and specificity (Table 2). In absence of 2-fluoro-4-methylphenol, discrimination was not possible between C. difficile positive and negative samples [20]. In addition, three other studies demonstrated that, by means of GC-MS, C. difficile positive fecal samples could be distinguished from controls based on their VOC profiles.…”
Section: Infectious Diseasesmentioning
confidence: 91%
“…However, results of culture are commonly obtained after at least 48 h, while rapid diagnosis is necessary to apply appropriate therapeutic interventions, such as prescription of targeted antibiotics and isolation of patients [18]. Most studies on application of fecal VOC analysis in infectious disease have focused on Clostridium difficile [19][20][21][22][23]. Other studies include detection of Campylobacter jejuni, cholera, giardiasis and rotavirus [21,[23][24][25][26].…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…So far, most of the reports involving SPME studies of bacteria have considered the diagnostic value of the method e.g. identification/confirmation of given bacteria in biological materials [68][69][70]. Recently, studies of E. coli employing a high throughput thin film SPME system focused on assessment of metabolome changes in bacteria influenced by the natural antibacterial agent cinnamaldehyde [71].…”
Section: Cell and Tissue Culturesmentioning
confidence: 99%
“…3-fluoro-4-hydroxyphenylacetic acid, resulted in the production of the VOC 2-fluoro-4-methylphenol, thus facilitating differentiation of the production of p-cresol by other species. In a blind study of 100 stool samples, 100 % of C. difficile positive stool samples could be correctly identified by this methodology [27].…”
Section: Use Of Enzyme Substrates To Liberate Exogenous Vocsmentioning
confidence: 99%
“…Another study, by the same group, involved the development of a novel VOC assay for the detection of Clostridium difficile in stool samples by inclusion of VOC liberating enzyme substrates and selective antibiotics in a liquid growth medium [27], in conjunction with a sample pre-treatment step to eliminate competing microflora. By subjecting the stool samples to alcohol (ethanol) shock the large number of microflora present in a stool sample were killed leaving only spores of C. difficile.…”
Section: Use Of Enzyme Substrates To Liberate Exogenous Vocsmentioning
confidence: 99%